Comparative study on dynamic visual tracking abilities in three-dimensional multi-object tracking tasks among basketball players of different skill levels - Guo, Zhi; Wang, Qiulin (Frontiers in Psychology, 2025)
ObjectiveThis study aimed to examine whether high-level basketball players exhibit superior multi-object tracking abilities compared to low-level basketball players using the three-dimensional multi-object tracking (3D-MOT) task paradigm.MethodsForty-eight participants (24 high-level and 24 low-level basketball players) from a university in Jiangsu were recruited. A 2 × 4 mixed experimental design was employed, with group (high vs. low) and tracking load as independent variables, and reaction time and accuracy in the 3D-MOT task as dependent variables.ResultsThe main effect of tracking load was significant, with tracking accuracy showing a linear decrease as the number of targets increased. The main effect of athletic level was also significant: while both groups showed reduced performance with increasing target numbers, high-level basketball players maintained higher accuracy and shorter reaction times under greater tracking loads.ConclusionHigh-level basketball players outperformed low-level basketball players in multi-object tracking tasks, demonstrating superior adaptability and stability in dynamic visual information processing. Specifically, they maintained more accurate and efficient tracking performance when faced with complex task demands.